Role of single-dose intravenous iron therapy for the treatment of anaemia after orthopaedic trauma: protocol for a pilot randomised controlled trial - Martin A Schreiber; Danielle F Peterson; Natasha S McKibben; Catherine E Hutchison; Karalynn Lancaster; Chih Jen Yang; Graham J Dekeyser; Darin M Friess; Nick J Willett; Joseph J Shatzel; Joseph E Aslan; Zachary M Working (BMJ Open)
Introduction Orthopaedic trauma and fracture care commonly cause perioperative anaemia and associated functional iron deficiency due to a systemic inflammatory state. Modern, strict transfusion thresholds leave many patients anaemic; managing this perioperative anaemia is an opportunity to impact outcomes in orthopaedic trauma surgery. The primary outcome of this pilot study is feasibility for a large randomised controlled trial (RCT) to evaluate intravenous iron therapy (IVIT) to improve patient well-being following orthopaedic injury. Measurements will include rate of participant enrolment, screening failure, follow-up, missing data, adverse events and protocol deviation.Methods and analysis This single-centre, pilot, double-blind RCT investigates the use of IVIT for acute blood loss anaemia in traumatically injured orthopaedic patients. Patients are randomised to receive either a single dose infusion of low-molecular weight iron dextran (1000 mg) or placebo (normal saline) postoperatively during their hospital stay for trauma management. Eligible subjects include adult patients admitted for lower extremity or pelvis operative fracture care with a haemoglobin of 7–11 g/dL within 7 days postoperatively during inpatient care. Exclusion criteria include history of intolerance to intravenous iron supplementation, active haemorrhage requiring ongoing blood product resuscitation, multiple planned procedures, pre-existing haematologic disorders or chronic inflammatory states, iron overload on screening or vulnerable populations. We follow patients for 3 months to measure the effect of iron supplementation on clinical outcomes (resolution of anaemia and functional iron deficiency), patient-reported outcomes (fatigue, physical function, depression and quality of life) and translational measures of immune cell function.Ethics and dissemination This study has ethics approval (Oregon Health & Science University Institutional Review Board, STUDY00022441). We will disseminate the findings through peer-reviewed publications and conference presentations.Trial registration number NCT05292001; ClinicalTrials.gov.